2022
DOI: 10.1371/journal.pone.0276984
|View full text |Cite
|
Sign up to set email alerts
|

Annona muricata L. peel extract inhibits carbohydrate metabolizing enzymes and reduces pancreatic β-cells, inflammation, and apoptosis via upregulation of PI3K/AKT genes

Abstract: Background and objective Annona muricata L. peel has been recognized for many ethnobotanical uses, including diabetes management. However, limited detailed scientific information about its mechanism of antidiabetic activity exists. The objective of this study was to evaluate the anti-diabetic properties of an aqueous extract of A. muricata peel (AEAMP) and its mechanism of action on alloxan-induced diabetic rats. Methods In vitro antidiabetic assays, such as α-amylase and α-glucosidase were analyzed on AEAMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…In the liver, glucokinase is involved in the process of glucose store as glycogen. The effect of MEOAL on the inhibition α-glucosidase and α-amylase activity displayed to be concentration dependent indicating the potential activity of extract’s antidiabetic action [ 52 ]. Through in silico modelling six compounds in MEOAL are shown to bind to pancreatic alpha-amylase and glucokinase protein with Catechin, Kaempferol, and Epicatechin showing a highest binding affinities.…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, glucokinase is involved in the process of glucose store as glycogen. The effect of MEOAL on the inhibition α-glucosidase and α-amylase activity displayed to be concentration dependent indicating the potential activity of extract’s antidiabetic action [ 52 ]. Through in silico modelling six compounds in MEOAL are shown to bind to pancreatic alpha-amylase and glucokinase protein with Catechin, Kaempferol, and Epicatechin showing a highest binding affinities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the effect of selected A. muricata active compounds (rutin, muricatocin A, anonaine, isolaureline, xylopine, and kaempferol 3-O-rutinoside) on inhibition of the Forkhead Box O1 (FOXO1) protein, and the results revealed that FOXO1 protein plays a crucial role in the proliferation process of pancreatic β-cells and inhibition of the FOXO1 protein activity in the nucleus will enhance insulin sensitivity [33,34]. Furthermore, a study has reported that an aqueous extract of A. muricata peel (AEAMP) inhibited α-amylase and α-glucosidase enzymes more effectively than acarbose, and that it improve β-cell dysfunction by upregulating liver AKT and pancreatic PI3K and AKT genes, and preventing apoptosis by upregulating liver and pancreatic Bcl2 [35].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible way to induce β-cell apoptosis is to inhibit the function of Akt, which is a serine/threonine kinase. First, it was shown that Akt could increase cellular proliferation, but that its inhibition could induce apoptosis ( 142 ). Second, Akt upregulates CDKN1B to trigger apoptosis while adversely regulating the transcriptional activity of FOXO1 ( 143 ).…”
Section: Mechanism Of Ceramides In Diabetesmentioning
confidence: 99%